Kappa, Tengu, dan Model Pandangan Masyarakat Jepang terhadap Orang Asing - Wibowo, Robi (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2023)
The problem that is most often discussed in intercultural relations between nations is the problem of the views of the domestic community towards immigrants, or vice versa. Japanese people in their lives are also very colored by this fact, which is always building awareness about the boundaries between themselves and foreigners. There are many academic facts that attempt to explain this view. However, the results of the study still present very long explanations and contain complex ambiguities. In these studies, a simple model that is easier to understand is not found. Therefore, this study seeks to find a model (logic of thinking) through the structural unconscious that resides in its fairy tales. The tales that will be studied are a collection of Kappa tales and Ten'gu tales. To explore the structural unconscious, this study will use Levi-Strauss' structural theory. With this theory, the analysis will lead to the discovery of the inner structure of the fairy tale, which is nothing but a model or logic of people's thinking. From the analysis, a model can be generated that shows the reasons for how Japanese people welcome or do not welcome foreigners. This model also overcomes complicated/ambiguous explanations from previous studies.